1992
DOI: 10.1007/bf01840840
|View full text |Cite
|
Sign up to set email alerts
|

Proportional hazards and recursive partitioning and amalgamation analyses of the southwest oncology group node-positive adjuvant CMFVP breast cancer data base: a pilot study

Abstract: Several putative prognostic factors have been identified in node-positive breast cancer patients, but their importance needs to be clarified in a uniformly treated population. The objectives of this investigation were: 1) to describe the characteristics of a uniformly treated node-positive data base; 2) to use proportional hazards (Cox) and recursive partitioning and amalgamation (RPA) multivariate models to assess the importance of potential prognostic factors for disease-free and for overall survival; and 3)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

1994
1994
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…We used the Euclidean distance, which is representing the distance between pixels associated with leaf nodes N i and N j : 2 (1)…”
Section: Distance-map Computationmentioning
confidence: 99%
See 3 more Smart Citations
“…We used the Euclidean distance, which is representing the distance between pixels associated with leaf nodes N i and N j : 2 (1)…”
Section: Distance-map Computationmentioning
confidence: 99%
“…We used a distance equal to 40 as the upper limit, which is based on the clinical equivalent requirement of having micro-calcifications clustered within 1cm 2 . 2 The resulting representation for the RoIs is a set of trees, some of which have depth ≤ 1 (i.e. either individual microcalcifications which are not connected or a group of 2 connected micro-calcifications), whilst others have depth ≥ 2 (i.e.…”
Section: Constructing Trees From Closest Nodesmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies [1][2][3][4][5][6][7][8][9][10][11] have shown the prognostic value of patient age at diagnosis and have suggested aggressive systemic treatment after surgery for young breast cancer patients [8]. In contrast, since young breast cancer patients are believed to have a similar prognosis to older patients, the management of young breast cancer patients should be decided using standard criteria [12][13][14].…”
Section: Introductionmentioning
confidence: 99%